Governance and Water Management: Progress and Tools in Mediterranean Countries - Alessandra Sgobbi; Gregorio Fraviga (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper reviews the progress with respect to Integrated Water Resource Management (IWRM) in Mediterranean countries, as addressed within the activities of the Nostrum-Dss project, a Coordination Action funded by the 6th Framework Programme of the EC, with a particular emphasis on the current use of decision support tools (DSS). The IWRM paradigm is a comprehensive management framework, which integrates the different aspects of water resources from the underlying ecological and physical aspects, to the socio-economic values and needs (horizontal integration); and calls for increasing decentralisation and privatisation of water services (vertical integration), and the devolution of planning authority, without however forgetting the need to ensure equitable access to water resources. Substantial progress has been made in the last decades in Nostrum-Dss Partner countries, although a disparity can still be seen between the Northern and Southern banks. New institutions have been established for implementing IWRM, existing institutions have been reformed, and decision making processes increasingly require public participation. Decentralisation of decision making, implementation and monitoring are also well underway, although improvements are still needed to ensure that the traditional power structures do not prevail. More efficient technologies and infrastructures are in place, especially for the production of high value goods or in agriculture. Finally, several DSS have been developed: yet, while operational/technical DSS instruments have been successfully employed, DSSs tools developed in a participatory way, or tackling more complex, political as well as environmental and economic problems are still de-linked from actual decision making processes. Laws and regulations for water management in most Mediterranean countries embrace and support the paradigms of IWRM and EU framework directives have played an important role in fostering this shift from more traditional, vertical governance to new, horizontal governance based on soft laws. Yet, the implementation of such laws and regulations is often only partial often because of the lack of a clear monitoring and enforcement strategy, but also because of governments financial and human resources constraints. Strong overlaps of roles and competences among different government institutions remain, hampering effective implementation of water management. The tendency to centralisation of decision making persists, and actors involvement is scanty. The shift towards the use of demand side policies as opposed to supply side policies is not yet completed: yet, supply side policies are very costly, as they are based on greater mobilisation of financial resources. Full cost recovery pricing is not practiced widely. This reluctance to introduce full cost recovery pricing in developing countries may be due to ethical and moral considerations, but in developed countries it is often associated with strong lobbying power of interest groups. This study was supported by funding under the Sixth Research Framework of the European Union within the project Network on Governance, Science and Technology for Sustainable Water Resource Management in the Mediterranean- The role of Dss tools (NOSTRUM-Dss, contract number INCO-CT-2004-509158).
Keywords: Q01; Q25; Q28; 330; Integrated Water Resources Management; Decision Support Systems; Environmental Governance